Magnetic wrinkled organosilica-based metal-enzyme integrated catalysts for enhanced chemoenzymatic catalysis - Yunting Liu; Na Guo; Weixi Kong; Shiqi Gao; Guanhua Liu; Liya Zhou; Jing Gao; Yanjun Jiang (Green Synthesis and Catalysis, 2024)
Core-shell structured magnetic wrinkled organosilica-based metal-enzyme integrated catalysts were synthesized, and their catalytic performances were studied in the chemoenzymatic dynamic kinetic resolution of chiral amines in an organic solvent, as well as in the chemoenzymatic synthesis of chiral alcohols in water. Structure-performance studies revealed the important influence of their tunable structure and composition on the optimization of activity, stability, and recyclability in chemoenzymatic catalysis.